Personality disorders – farewell to DSM IV and ICD-10 Part I: General principles for the diagnosis of personality disorders according to DSM-IV and ICD-10. Cluster A of DSM-IV personality Disorders - Czernikiewicz, Andrzej; Baran, Tetiana (Current Problems of Psychiatry, 2013)
In May of this year, the long-awaited diagnostic tool has been launched in the "diagnostic market," which will be the next version of the manual of the American Psychiatric Association - DSM-5. Changes in personality disorders are quite revolutionary, so I decided to bring the clinical description of personality disorders still in the current diagnostic manuals, i.e. the ICD-10 and DSM-IV.In future editions of our journal the description of personality disorder according to ICD-10 and DSM-IV will be presented. In the fourth and fifth parts we are planning to introduce a new definition of personality disorders according to DSM-5. The first part presents the general aspects and diagnosis of personality disorders and disorders of the Cluster A: paranoid, schizotypal and schizoid.